Closing the Gap : Expanding Access to Social Services - Pyne, Hnin Hnin; Dutta, Puja Vasudeva; Sondergaard, Lars; Stevens, James; Thwin, Mar Mar; Kham, Nang Mo (World Bank, Yangon, 2016)
Myanmar has an important opportunity to improve the health status and education outcomes of its people after decades of underspending and institutional neglect in the social sectors. Low access to health, education and social protection services has severely worsened human development outcomes, which ranked among the lowest in the region. Since 2011, there has been a sea change in public policy with rapidly rising social spending to expand access to services and protect families from poverty. The payoffs are immense, in Myanmar, an additional year of schooling is estimated to be associated with 6.7 percent higher income (World Bank, 2014a), which will be compounded with better health and social protection. Although significant progress has been made recently, immense challenges and opportunities remain. Policies to close the gap in access to social services are fundamental to inclusive growth in Myanmar.